2013
DOI: 10.1021/am302728m
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-Induced Self-Healing of a Microcapsule-Type Protective Coating

Abstract: Photopolymerization behavior of a methacryloxypropyl-terminated polydimethylsiloxane (MAT-PDMS) healing agent was investigated in the presence of benzoin isobutyl ether (BIE) photoinitiator by Fourier transform infrared (FT-IR) spectroscopy. MAT-PDMS and BIE were microencapsulated with urea-formaldehyde polymer. The surface and shell morphology of the microcapsules was investigated by scanning electron microscopy (SEM). Mean diameter and size distribution of the microcapsules could be controlled by agitation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(115 citation statements)
references
References 27 publications
1
112
0
2
Order By: Relevance
“…The formulation and microcapsules were then mixed, resulting in a self-healing coatingformulation. A use involved spraying of the coatingformulation onto the surface of a board made of cellulosefiber-reinforced-cement and a motar [52]. It was revealed that the healing agent could be released from the ruptured microcapsules and then filled the are where the damage occured, and a sunlight-induced self-healing capability was also demonstrated during the tests on the motar.…”
Section: Self-healing Coatings For Corrosion Protectionmentioning
confidence: 99%
“…The formulation and microcapsules were then mixed, resulting in a self-healing coatingformulation. A use involved spraying of the coatingformulation onto the surface of a board made of cellulosefiber-reinforced-cement and a motar [52]. It was revealed that the healing agent could be released from the ruptured microcapsules and then filled the are where the damage occured, and a sunlight-induced self-healing capability was also demonstrated during the tests on the motar.…”
Section: Self-healing Coatings For Corrosion Protectionmentioning
confidence: 99%
“…Verify capsule core structure: weigh a small amount of silicone polyether microcapsule samples to two sheets of a piece of clean glass, provide the existence of oily phase in the sample microcapsule by squeezing and observe the oil phase overflowing [7] .…”
Section: Verify the Capsule Core Structurementioning
confidence: 99%
“…In one international study, self-healing materials and catalysts were encapsulated as microsized capsules [5,6]. Meanwhile, in Korea, selfhealing microsized capsules capable of reacting with sunlight or moisture without catalysts have been applied in actual construction [7]. Two conclusions can be derived from these case studies at home and abroad.…”
Section: Introductionmentioning
confidence: 99%